High Sensitivity Near‐Infrared Imaging of Fluorescent Nanosensors. Issue 14 (6th January 2023) - Ackermann, Julia; Stegemann, Jan; Smola, Tim; Reger, Eline; Jung, Sebastian; Schmitz, Anne; Herbertz, Svenja; Erpenbeck, Luise; Seidl, Karsten; Kruss, Sebastian
Abstract: Biochemical processes are fast and occur on small‐length scales, which makes them difficult to measure. Optical nanosensors based on single‐wall carbon nanotubes (SWCNTs) are able to capture such dynamics. They fluoresce in the near‐infrared (NIR, 850–1700 nm) tissue transparency window and the emission wavelength depends on their chirality. However, NIR imaging requires specialized indium gallium arsenide (InGaAs) cameras with a typically low resolution because the quantum yield of normal Si‐based cameras rapidly decreases in the NIR. Here, an efficient one‐step phase separation approach to isolate monochiral (6, 4)‐SWCNTs (880 nm emission) from mixed SWCNT samples is developed. It enables imaging them in the NIR with high‐resolution standard Si‐based cameras (>50× more pixels). (6, 4)‐SWCNTs modified with (GT)10 ‐ssDNA become highly sensitive to the important neurotransmitter dopamine. These sensors are 1.7× brighter and 7.5× more sensitive and allow fast imaging (<50 ms). They enable high‐resolution imaging of dopamine release from cells. Thus, the assembly of biosensors from (6, 4)‐SWCNTs combines the advantages of nanosensors working in the NIR with the sensitivity of (Si‐based) cameras and enables broad usage of these nanomaterials. Abstract : (6, 4)‐single‐wall carbon nanotubesfluoresce in the near‐infrared (NIR, 880 nm) and can be chemically functionalized with DNA to act as sensors. They provide access to the sweet spot between the efficiency of (Si) cameras of standard microscope equipment and the advantages of NIR, which is shown by high‐resolution mapping of dopamine release from cells.